Collaboration Strategies in Counteraction to Global Threats - F. Galindo; E. Gursky; N. V. Dmitrienko; D. A. Ghuravlev; R. Laporte; F. Y. Linkov; N. L. Mikhailov; A. Rossodivita; C. Tomljanovich; A. I. Trufanov; E. Photiou; E. Vl. Shubnikov (Безопасность информационных технологий, 2010)
Topology of information sharing networks in emergency situations and creation of stable relations between pertinent national and international agencies has been studied. Agent-based simulation model with competitive and collaborative actors has been developed to perform a quantitative analysis of interagency and international cooperation . It has been demonstrated a great value of action to support links between middle rank agents to counteract global threats effectively.